1998
DOI: 10.1105/tpc.10.7.1207
|View full text |Cite
|
Sign up to set email alerts
|

A High-Conductance Solute Channel in the Chloroplastic Outer Envelope from Pea

Abstract: The pea chloroplastic outer envelope protein OEP24 can function as a general solute channel. OEP24 is present in chloroplasts, etioplasts, and non-green root plastids. The heterologously expressed protein forms a voltage-dependent, high-conductance ( ⌳ ‫؍‬ 1.3 nS in 1 M KCl), and slightly cation-selective ion channel in reconstituted proteoliposomes. The highest open probability ( P open Ϸ 0.8) is at 0 mV, which is consistent with the absence of a transmembrane potential across the chloroplastic outer envelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…This is probably not as simple since substrate-specific gated pore-forming proteins were characterized in the outer envelope membrane (Pohlmeyer et al 1997(Pohlmeyer et al , 1998Bölter et al 1999;Goetze et al 2006;Hemmler et al 2006). Altogether, the combined proteomic and in silico approaches suggest that a series of known or putative transport systems are likely to be localized in the chloroplast envelope (Seigneurin-Berny et al 1999;Ferro et al 2002;Weber et al 2005).…”
Section: Envelope Proteins and The Ionic/metabolic Dialog Between Plamentioning
confidence: 94%
“…This is probably not as simple since substrate-specific gated pore-forming proteins were characterized in the outer envelope membrane (Pohlmeyer et al 1997(Pohlmeyer et al , 1998Bölter et al 1999;Goetze et al 2006;Hemmler et al 2006). Altogether, the combined proteomic and in silico approaches suggest that a series of known or putative transport systems are likely to be localized in the chloroplast envelope (Seigneurin-Berny et al 1999;Ferro et al 2002;Weber et al 2005).…”
Section: Envelope Proteins and The Ionic/metabolic Dialog Between Plamentioning
confidence: 94%
“…In addition, OEP24 appears to be related to the major mitochondrial solute channel, the voltage-gated anionselective channel protein VDAC (Pohlmeyer et al, 1998). OEP24 displays similar specificity characteristics and it can complement a yeast VDAC mutant strain (Rö hl et al, 1999).…”
Section: Pore Proteins Of the Chloroplast Outer Envelopementioning
confidence: 97%
“…OEP16 is a cation-selective channel with a selectivity for amino acids and amines (Pohlmeyer et al, 1997), whereas OEP21 is an intrinsic-rectifying anion-selective channel specific for inorganic phosphates, triosephosphates, and 3-phosphoglycerate (Bö lter et al, 1999). OEP24 also allows the passage of triosephosphates, ATP, and inorganic phosphates as well as both cation and anions (Pohlmeyer et al, 1998). Very little is known so far about the characteristics of OEP7 or OEP37.…”
Section: Pore Proteins Of the Chloroplast Outer Envelopementioning
confidence: 99%
“…Numerous substrate-specific transporters in the plastid inner envelopes again reflect this metabolic interdependence (Flu¨gge 1998). Recently, evidence has accumulated that the chloroplast outer envelope contains different solute-selective ion channels (Pohlmeyer et al 1998a(Pohlmeyer et al , 1998bBo¨lter et al 1999;Bo¨lter and Soll 2001). These data indicated that the outer envelope functions as a selective molecular filter rather than an unspecific sieve that runs by size-exclusion only.…”
Section: Introductionmentioning
confidence: 96%